Priority focused medium access control in wireless sensor actuator networks for CPS. (2016) - Sultana, H. Parveen; Krishna, P. Venkata
In cyber physical systems (CPSs), wireless sensor actuator networks (WSANs) play a major role in interconnecting the physical world through wireless devices. It is considered that MAC protocol 802.15.4 is an appropriate protocol for CPSs environment. In this paper, we proposed a medium access control procedure with priority called virtually prioritised backoff procedure (VPBP). Smart nodes involved in this network are initially assigned a priority according to its functionality. A smart node with highest priority is accessed by the centre node (coordinator) initially. If a priority of node is equal then by assigning a fair chance, a starving node with highest critical value is allowed to transmit the data. This is to overcome the disadvantage of traditional 802.15.4 carrier sense multiple access with collision avoidance (CSMA/CA) method. Finally, we have proved with the simulation results that the VPBP approach has reduced the collisions in a CPS based wireless networks.